A Review of Siyasah Fiqh on the Implementation of Regional Regulation Number 5 of 2012 Tangerang City - Ebta Yulianto; Siti Ngainnur Rohmah (UIN JAKARTA, 2022)
Regardless of the size of a city, children living on the streets, the homeless, and begging have become typical aspects of city life. This issue appears to necessitate particular attention. The problems of unmanaged homelessness, street kids, and begging are also present in Tangerang. The purpose of this study was to determine the extent to which the fiqh siyasah has evaluated regional rule 5 of 2012 in Tangerang City. This inquiry utilizes library searches with a policy-centric focus. This study discovered that Law No. 11 of 2009 concerning Social Health and Law No. 13 of 2012 concerning Handling the Poor are used to implement the Tangerang City Regulation, which promotes the right to education, shelter, and work for street children, homeless persons, beggars, and buskers. Numerous aspects of Tangerang City Regulation Number 5 of 2012 are consistent with siyasa fiqh, including the obligation to protect all people regardless of race or religion, the protection of oneself, one's property, and one's family, and the emphasis on equality of rights and equality before the law. In accordance with the Siyasah fiqh principles espoused by Abdul Khalaf Wahhab and Abu A'la al-Maududi, Regional Regulation No. 5 of 2012 also seeks to preserve the human rights of each community, social justice, and legal protection for all.